Sustainability in Contemporary Visual Arts: Trends and Applicability (Al-Academy, 2024)
The world today is witnessing many changes, developments and challenges that have necessitated the adoption of various methods that follow a scientific approach to contribute to the societal development by focusing on the concept of sustainability to meet the needs of society according to environmental resources. Visual arts are a creativejs field that can achieve the concept of sustainability. The current study address the concept of sustainability in contemporary visual arts, as it aims to identify the concept, and clarify its dimensions in visual arts to reveal trends and possibilities for applying sustainability in contemporary arts fields. The study followed the descriptive analytical approach, and the sample intentionally included four artworks. The study concluded that many contemporary artworks Rely on the intellectual dimensions of the concept of sustainability, and highlights creativity of many contemporary artists in applying the concept of sustainability in artistic creation